The assessment of the genetic improvement of South African composite breeds and their respective foundation breeds - Van Marle-Koster, Este (University of Pretoria, 2023)
Dissertation (MSc (Agric Animal Science: Animal Breeding and Genetics))--University of Pretoria, 2023.